Cattle Feeding and Management Practices at Delduar Upazila in Tangail District of Bangladesh: Cattle feeding and management practices - Md Ratan; Shanaz Alam Sunny; Md Mufazzal Hossain; Mofassara Akter; Md Imran Hossain (Research in Agriculture Livestock and Fisheries, 2025)
This study examines the cattle management practices and challenges faced by smallholder cattle farmers at Delduar upazila in Tangail District of Bangladesh during the period from July 2023 to June 2024. The average number of cattle per farm varied, with large-scale farms (>25 cattle) averaging 27 cattle, while small-scale farms (1-5 cattle) averaged 3.40 cattle. Housing space per cattle was inversely proportional to farm size, with small farms providing more space per animal. Concrete sheds were predominant (47.5%) and rice straw was the most common roughage feed (100%). Concentrate feeds mainly included rice bran (92.5%). Smart Napier grass was the most cultivated green grass (40%). The study also assessed the amount of feed supplied, with larger farms providing more green grass and concentrate per cattle daily. Average milk production per cow increased with farm size, peaking at 7 liters. Antibiotics and feed additives were less commonly used compared to deworming practices. Common diseases included FMD and LSD, with vaccination practices varying across farm sizes. Training experience was reported by 67.5% of farmers. Key challenges identified were high feed prices and lack of proper knowledge, with farmers suggesting cost reduction and improved veterinary services as primary solutions. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 35-44